Morpho-phylogeny characterization of Linocarpon bambusina sp. nov. (Linocarpaceae, Chaetosphaeriales) associated with bamboo in Yunnan Province, China - Zhang, Xian; Dai, Dongqin; Du, Tianye; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2023)
Yunnan Province (China) is one of the most bamboo-rich regions in the world. In this study, a saprophytic fungus was collected from dead bamboo in Yunnan Province. Based on molecular phylogenetic analyses of combined LSU, SSU, and tef1-α sequence data, our collections grouped within Linocarpon and formed a separate clade with high statistical support. The morphological comparison showed that our collections has some characteristics such as semi-immersed ascomata, fusiform asci, and ascospores with 28–30 septa, which are different from other species in Linocarpon. Therefore, based on morpho-phylogenetic evidence, our collection is identified as a new bambusicolous species in China and named Linocarpon bambusina sp. nov. A full description, photo plate, and a phylogenetic tree are provided for the new species.